Antioxidant Potential Profile of Extracts from Different Parts of Black Mulberry - IQBAL, SADAF; NADEEM ASGHAR*†, MUHAMMAD; ULLAH KHAN, ISLAM; ZIA, IRAM (Asian Journal of Chemistry, 2009)
Present study is aimed to exploit a potent and cheaper natural sources of antioxidants. Morus nigra L. is considered to be an antidiabetic and diuretic agent in the folk medicinal system of Indo-Pak subcontinent. Antioxidant potential and radical scavenging activity of the various organic and aqueous extracts of leaves, stem and fruit of M. nigra were investigated using 2,2'- azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) decolourization assay, ferric reducing antioxidant power (FRAP) assay, 2.2'-diphenyl-1-picrylhydrazyl (DPPH) assay, total phenolic content (TPC) assay and total antioxidant activity assay. Using ABTS•+ decolourization assay and FRAP assay, M. nigra extracts showed a wide range of antioxidant activity. Using TPC assay the amount of total phenolics ranged from 1.3048 to 5.8287, 0.413 to 2.9394 and 0.5346 to 6.2266 mg/L for different fractions of leaves, stem and fruit of M. nigra, respectively. Good co-relation was found between TPCs and TEAC values determined by ABTS•+ decolourization assay (r2 = 0.977, 0.943 and 0.823 for leaves, stem and the fruit of stem and FRAP assay (r2 = 0.887, 0.842 and 0.773 for leaves, stem and the fruit) of M. nigra. Employing total antioxidant assay using linoleic acid emulsion system, methanol, 1-butanol, aqueous and ethyl acetate fractions of all the parts of M. nigra showed strong peroxyl radicals scavenging activity. The data obtained by employing antioxidant and radical scavenging assays demonstrated the effectiveness of all the parts of M. nigra as antioxidative and radical scavenging which may also be correlated with its anti-disease activity in in vivo.